Designing of a novel polyvinylidene fluoride/TiO2/UiO-66-NH2 membrane with photocatalytic antifouling properties using modified zirconium-based metal-organic framework - Yi-Jing Li (IWA Publishing, 2021)
Novel polyvinylidene fluoride/TiO2/UiO-66-NH2 (PVDF/TiUN) membranes were produced by the delay phase separation method via introducing the TiO2/UiO-66-NH2 (TiUN) nanocomposite into PVDF casting solution. Interconnection of TiO2 and UiO-66-NH2 improved photocatalysis capacity and endowed PVDF/TiUN membranes with self-cleaning capability. Quantitative measurements showed that, firstly, PVDF/TiUN membranes exhibited improved photodegradation kinetics and efficiency (up to 88.1%) to Rhodamine B (RhB). Secondly, the performances of bovine serum albumin (BSA) rejection and permeation of PVDF/TiUN membranes outperformed those of other check samples, indicating enhanced hydrophilicity. Thirdly, rejection rate of BSA reached a breathtaking 98.14% and flux recovery ratio (FRR) of BSA reached a breathtaking 95.37%. Thus, given their excellent anti-contamination property and separation performance, the PVDF/TiUN membrane is very likely to be a novel water treatment membrane. HIGHLIGHTS PVDF/TiUN membrane was prepared for the first time via phase separation process method.; The membrane exhibits excellent antifouling performance with flux recovery ratio of almost 100%.; PVDF/TiUN membrane showed better removal performance under light conditions.; Visible light cleaning of fouled membranes enabled high recovery of membrane performance.;